Piloting a questionnaire on affective factors influencing willingness to communicate in English among Chinese undergraduates at a Malaysian university - Lyu, Yunhe; Abd Razak, Fatin Nabilah; Ahmad Sani, Nurshafawati; Abdullah, Ain Nadzimah (Universiti Teknologi MARA, 2025)
This paper reports on a pilot study evaluating the clarity, reliability, and feasibility of a questionnaire designed to assess affective factors impacting Chinese undergraduates’ Willingness to Communicate (WTC) in English at a Malaysian university. The research sought to understand their relationship with WTC by focusing on self-perceived communication competence (SPCC), communication apprehension (CA), motivation, and attitudes toward English. The questionnaire comprised five constructs covering relevant constructs. First, it seeks to assess the internal consistency, clarity, and contextual suitability of a 5-part questionnaire. Second, it provides preliminary insights into the affective profile of Chinese undergraduates in Malaysia as it relates to English communication. A sample of 45 Chinese undergraduates participated in this study. Results showed acceptable reliability (Cronbach’s alpha > .70) and highlighted the questionnaire’s suitability for the target population. Participant feedback improved item clarity and cultural relevance. This paper underscores the importance of piloting to validate instruments, especially in diverse educational settings, and shares lessons learned in instrument design and cultural adaptation.